(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Oncological outcomes of sphincter-saving resection (SSR) and sphincter losing abdominoperineal resection (APR) in 210 consecutive patients with very low-lying rectal cancer (i.e. lower margin of tumor is within 3.5 cm from the anal verge) were studied and compared. 54 (25.71%) patients underwent SSR and 156 (74.28%) patients underwent SLR-APR. The APR group comprised higher proportions of men (61.53% vs 55.5%, P =.049) and advanced-stage disease (P <.001). Preoperative chemoradiotherapy (PCRT) was administered in both the group with almost similar distribution (62.82 % vs 59.25%, P <.001). Overall, (the systemic and local) recurrence rates were almost similar i.e. 33.31% in SSR and 33.32% in APR. On stratification according to PCRT and pathologic stage, the mode of surgery did not affect the recurrence type. Moreover, recurrence-free survival (RFS) did not differ according to the mode of surgery in different cancer stages. Patients who were stratified according to cancer stage and PCRT also showed no differences in RFS according to the mode of surgery. The results of the study demonstrate that, regardless of PCRT administration, SSR is an effective treatment for very low rectal cancer. J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 3-8